2015
DOI: 10.4172/2379-1764.1000131
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Peptide Nucleic Acid

Abstract: Peptide Nucleic Acid (PNA) is a nucleobase oligomer in which the whole backbone is mainly replaced by N-(2aminoethyl) glycine units. PNA is considered as DNA with a neutral peptide backbone due to negative charged sugar-phosphate backbone. It is chemically stable and resistant to hydrolytic cleavage. PNA can be categorized specific sequences of DNA and RNA according to Watson-Crick hydrogen bonding structure. Hybridization process showed high thermal stability and unique ionic strength effects. It is formed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 86 publications
1
24
0
Order By: Relevance
“…PNA is chemically stable and is resistant to hydrolytic cleavage by nucleases or proteases. (Siddiquee et al, )…”
Section: Resultsmentioning
confidence: 99%
“…PNA is chemically stable and is resistant to hydrolytic cleavage by nucleases or proteases. (Siddiquee et al, )…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these problems, new synthetic methodologies and development of various derivatives have been proposed. Most of these derivatives were designed to increase complementary binding capacity and cell permeability by introducing a new functional group into the peptide backbone or modifying DNA bases . Recently Israel researchers have found that a PNA dimer forms a specific quaternary structure by self‐replication of bases at a specific pH and exhibits a unique fluorescence property, which can be used as an organic light‐emitting diode (OLED) device.…”
Section: Methodsmentioning
confidence: 99%
“…PNA is neither a nucleic acid nor a protein and it can withstand both nucleases and proteases; so has become a potential biomolecular tool with a superior lifetime for in vivo and in vitro applications such as, molecular diagnostics and antisense therapeutics (Janson and During, 2006). Although many researchers have reviewed the PNA chemistry, (Siddiquee et al, 2015;Veldhoen et al, 2008) their modifications (Rozners, 2012;Sugiyama and Kittaka, 2013;Moccia et al, 2016), properties (Järver et al, 2012) and perspectives in molecular diagnostics (Shi et al, 2015), but in this review we are focusing on various properties of PNA along with special emphasis on its biomedical applications.…”
Section: Introductionmentioning
confidence: 99%